Interruption of Vif/Elongin C interaction: In silico and experimental elucidation of the underlying molecular mechanism of benzimidazole-based APOBEC3G stabilizers. Issue 8 (15th April 2020) - Radwan, Mohamed O.; Takaya, Daisuke; Koga, Ryoko; Iwamaru, Kana; Tateishi, Hiroshi; Ali, Taha F.S.; Takaori-Kondo, Akifumi; Otsuka, Masami; Honma, Teruki; Fujita, Mikako
Graphical abstract: Highlights: Compound MM-1 is a promising APOBEC3G stabilizer of elusive mechanism of action. Comprehensive in silico study revealed their potential to interrupt Vif/Elongin C binding. The prediction was validated through synthesis and biochemical in vitro assay of MM-1 . MM-1 proved an explicit negative impact on Vif/Elongin C interaction. Abstract: In 2014, two novel and promising benzimidazole-based APOBEC3G stabilizers MM-1 and MM-2 (MMs) were uncovered with an elusive mechanism of action. Vif-APOBEC3G axis has been recognized as a novel therapeutic target for anti HIV-1 drug development. The unexplored mechanism of MMs hindered their further development into lead compounds. To recognize their underlying mechanism we adopted an exhaustive in silico workflow by which we tested their ability to interrupt Vif complex network formation. The preliminary outcome guided us to a high likelihood of MMs interaction within Elongin C binding site, which in turn, perturbs Vif/Elongin C binding and ultimately undermines Vif action. To validate our estimation, we synthesized only MM-1 as a model to complement our study by in vitro assay for a real-time understanding. An immunoprecipitation experiment confirmed the capacity of MM-1 to interrupt Vif/Elongin C interaction. This is an integral study that lies at the interface between theoretical and experimental approaches showing the potential of molecular modelling to address issues related to drug development.